The geology of the Otjosondu manganese area: south west Africa - Roper, Harold (My University, 1959)
Geological mapping and compilation of data from mining and prospecting operations in the Otjosondu area in South West Africa provided the information presented in this thesis. The geomorphology of the area is described and the general geology is discussed. Details of the complicated folding suffered by the Iamara rocks are presented. The petrology and petrography of' the outcropping representatives of the ancient sedimentary and intrusive rocks is described under the section on economic geology, interpretations of the complex structures of the ore bodies are presented. The mineralogy of the ores was studied by means of polished sections, X-ray diffraction and differential thermal analysis techniques. It is concluded from both field and laboratory evidence that these ores represent the metamorphosed equivalents of syngenetic manganese bearing sediments
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Geology to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 1959